2012
DOI: 10.1371/journal.pone.0047244
|View full text |Cite
|
Sign up to set email alerts
|

L. plantarum, L. salivarius, and L. lactis Attenuate Th2 Responses and Increase Treg Frequencies in Healthy Mice in a Strain Dependent Manner

Abstract: Many studies on probiotics are aimed at restoring immune homeostasis in patients to prevent disease recurrence or reduce immune-mediated pathology. Of equal interest is the use of probiotics in sub-clinical situations, which are characterized by reduced immune function or low-grade inflammation, with an increased risk of infection or disease as a consequence. Most mechanistic studies focus on the use of probiotics in experimental disease models, which may not be informative for these sub-clinical conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
74
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 77 publications
12
74
0
Order By: Relevance
“…Clostridium sensu stricto was also elevated by sugar and has been correlated with the development of food allergy or food sensitization during early life (53,54) and atopic dermatitis during childhood (55). Lactobacillus, a strain of bacteria associated with promoting regulatory T helper cells (56) and preserving tight junctions in the epithelial cells of the intestinal tract (57), was increased by sugar consumption, whereas previous studies showed that this strain is reduced in mice fed an HFD (58)(59)(60)(61). Alistipes (genus in the family Rikenellaceae) and Bacteroides (genus in the family Bacteroidaceae) were also significantly elevated in all sugar groups compared with controls.…”
Section: Figurementioning
confidence: 99%
“…Clostridium sensu stricto was also elevated by sugar and has been correlated with the development of food allergy or food sensitization during early life (53,54) and atopic dermatitis during childhood (55). Lactobacillus, a strain of bacteria associated with promoting regulatory T helper cells (56) and preserving tight junctions in the epithelial cells of the intestinal tract (57), was increased by sugar consumption, whereas previous studies showed that this strain is reduced in mice fed an HFD (58)(59)(60)(61). Alistipes (genus in the family Rikenellaceae) and Bacteroides (genus in the family Bacteroidaceae) were also significantly elevated in all sugar groups compared with controls.…”
Section: Figurementioning
confidence: 99%
“…However, immunomodulation by probiotic bacteria in a simplified in vitro system or in an established inflammation model in vivo does not reflect effects in conditions of homeostasis. Only few studies have addressed the effects of probiotic bacteria in healthy subjects (24)(25)(26)(27), and substantial variability in the response of human subjects to probiotic intervention was found (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the beneficial effects of probiotics in inflammatory disease, the disease-preventing potential of probiotic bacteria is gaining attention [18][21]. Probiotic treatment may benefit individuals who are not yet receiving medical treatment, but are at risk of developing disease due to age- [22], obesity- [23], malnutrition- [24], or stress-related [25] deterioration of immune homeostasis.…”
Section: Introductionmentioning
confidence: 99%